2010
DOI: 10.1002/pssc.201000023
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐hydroxyapatite colloid suspension coated on chemically modified porous silicon by cathodic bias: a suitable surface for cell culture

Abstract: The properties of porous silicon make it an interesting material for biological applications. However, porous silicon is not an appropriate surface for cell growth. Surface modification is an alternative that could afford a bioactive material. In this work, we report a method to yield materials by modification of the porous silicon surface with hydroxyapatite of nanometric dimensions, produced using an electrochemical process and coated on macroporous silicon substrates by cathodic bias. The chemical nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…In agreement with the 13 C NMR spectra, 31 P NMR spectra (figure S3) (stacks.iop.org/BMM/10/055015/ mmedia) show complexation-induced chemical shifts (CSC) for the hydroxyapatite after the surface reactions have taken place. There is also an evidence for interaction between the organic molecules and the phosphate groups in the structure of probable ionic interactions [47][48][49][50][51].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In agreement with the 13 C NMR spectra, 31 P NMR spectra (figure S3) (stacks.iop.org/BMM/10/055015/ mmedia) show complexation-induced chemical shifts (CSC) for the hydroxyapatite after the surface reactions have taken place. There is also an evidence for interaction between the organic molecules and the phosphate groups in the structure of probable ionic interactions [47][48][49][50][51].…”
Section: Resultssupporting
confidence: 79%
“…The fact that hydroxyapatite is a biocompatible material highlights its potential for applications in biomedicine. In previous work, we have shown that porous silicon coated with hydroxyapatite did not show a cytotoxic effect on the Raw 264.7 macrophage cell line [31]. However, it has been widely documented that chemical modification of the surface of nanomaterials can influence their biological effect [32].…”
Section: Introductionmentioning
confidence: 94%
“…As an example, Bayliss et al ( 1997 , 1999 ) successfully grew B50 neurons and Chinese hamster ovary cells, being one the firsts reported in vitro experiments. Using an electrodeposition technique, Sánchez et al ( 2011 ) synthetized a PSi-HAP scaffold, which successfully supported murine macrophage cells (Figure 10 ). More recently, Hernandez-Montelongo et al ( 2014 ), using also an electrochemical deposition and a sol–gel technique, obtained two different kinds of PSi–CaP scaffolds.…”
Section: Cell Scaffolds Based On Porous Siliconmentioning
confidence: 99%
“… SEM images of (A) PSi–HAP scaffold (cross-sectional view), and (B) murine macrophages on PSi–HAP scaffold . Reprinted from Sánchez et al ( 2011 ). …”
Section: Cell Scaffolds Based On Porous Siliconmentioning
confidence: 99%
“…Additionally, it has been used as surface substrates for cell culture based on hydroxyapatite-PS [18] and intelligent implants [19]. For obtaining composites based on PS and HA, different deposition methods have been proposed [20–22].…”
Section: Introductionmentioning
confidence: 99%